Club activities in the modern Japan (Journal of Oriental Studies, 2018)
This article is devoted to a little-searched problem as activities of clubs in the modern Japan. Thepeculiarities of the Japanese education system are considered in the article, since the activities of clubsare closely linked with education. The categories and types of Japanese clubs are shown: bukatsudou,kurabu katsudou, sakuru katsudou. Differences in the work of clubs at various levels of education arerevealed: from the junior school to the university. A special place is given to the school council, whichmanages the activities of the clubs.